The didactive value of business games - Kovalenko, MSc. Natalia; Kovalenko, Ph. D. Kseniya (Revista Conrado, 2017)
Business games have recently gained immense popularity. In the process of preparing qualified specialists, active and interactive forms of training are widely used in the educational process in combination with out-of-class work. They are used in training high school students and students. In addition, with their help serious industrial, economic, managerial problems are solved, they are addressed when hiring new employees. Unfortunately, the theory of business games to date has not been sufficiently developed and is full of contradictions. Since a detailed description of each generalized technology is an independent problem, we stopped in his study on the characteristics of active learning and playing mostly pop type. The art of designing the educational process lies in the fact, to find a balance between the different pedagogical technologies. When designing the learning process through learning activities must be based on the idea of contextual learning. Keywords: Pedagogics, business game, values, training, modeling, simulation, activity, activity, teaching. RESUMEN Juegos de negocio recientemente han ganado una inmensa popularidad. En el proceso de preparación de especialistas cualificados, formas activas e interactivas de formación son ampliamente utilizados en el proceso educativo en combinación con el trabajo fuera de clase. Se utilizan en la formación de estudiantes de secundaria. Además, con su ayuda, graves problemas de gestión industriales, económicos se resuelven, se dirigen al contratar nuevos empleados. Por desgracia, la teoría de los juegos de negocio hasta la fecha no ha sido suficientemente desarrollada y está llena de contradicciones. Desde una descripción detallada de cada tecnología generalizada es un problema independiente, paramos en su estudio de las características del aprendizaje activo y jugando sobre todo tipo de pop. El arte de diseñar el proceso educativo radica en el hecho, para encontrar un equilibrio entre las diferentes tecnologías pedagógicas. Al diseñar el proceso de aprendizaje a través de actividades de aprendizaje debe basarse en la idea de aprendizaje contextual. Palabras clave: Pedagogía, juego de negocios, el valor, formación, la simulación, la simulación, la actividad, actividad, enseñanza.